Myeloid CD169/Siglec1: An immunoregulatory biomarker in viral disease - Herzog, Silva; Fragkou, Paraskevi C.; Arneth, Borros M.; Mkhlof, Samr; Skevaki, Chrysanthi (Frontiers in Medicine, 2022)
CD169, also known as Siglec1 or Sialoadhesin (Sn), is a surface adhesion molecule on human myeloid cells. Being part of the Siglec family, it acts as a receptor for sialylated molecular structures, which are found among various pathogenic and non-pathogenic ligands. Recent data suggest that CD169 may represent a promising new biomarker in acute respiratory and non-respiratory viral infections, such as SARS-CoV-2, Respiratory syncytial virus (RSV) and Human immunodeficiency virus (HIV). Therein lies a great potential to sufficiently differentiate viral from bacterial infection, which has been an incessant challenge in the clinical management of infectious disease. CD169 equips myeloid cells with functions, reaching far beyond pathogen elimination. In fact, CD169 seems to crosslink innate and adaptive immunity by antigen presentation and consecutive pathogen elimination, embodying a substantial pillar of immunoregulation. Yet, our knowledge about the kinetics, mechanisms of induction, signaling pathways and it´s precise role in host-pathogen interaction remains largely obscure. In this review, we describe the role of CD169 as a potentially novel diagnostic biomarker for respiratory viral infection by evaluating its strengths and weaknesses and considering host factors that are involved in pathogenesis of virus infection. Finally, this brief review aims to point out shortcomings of available evidence, thus, guiding future work revolving the topic.